(3ebOeI aj bQGAI GdbQBfs - (3eMeO Hf ESeGYjd GdMfajs
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai hHYO agPg ebOeI JJYdb HbQGAI GdbQBf ef MjK CfgG eTJedi Ydi HjGf eNGQL GdMQha hCMcGe Gdfhf GdSGcfI hGdJfhjf hCMcGe GdeO hHjGf MbjbI GdJLhjO s
(3BNQgG (B:s
(3hdG jLhR Gdhba EdG EPG cGf GdbGQF eVWQkG dcf jHJOF HGdcdeI GdJi hba YdjgG djRhd GdbHM JeJ s
(3GdfSNI HgG MhGTs
(3GfJgi ef JCdja cJGHg SfI (B983(3g`s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs